Wireless sensor nodes deployment using multi-robot based on improved spanning tree algorithm - Arezoumand, Reza (2015)
A wireless sensor network is a network consisting of a large number of sensor nodes deployed in a region to fulfil the demanding task of sensing. By merging wireless sensor nodes with mobile robots, the performance of wireless sensor network applications may be improved. Coverage and connectivity are the two parameters of a wireless sensor network. Stochastic node deployment or random node deployment may cause holes in sensing coverage and existing redundant nodes in the area. On the other hand, precise deployment of nodes in large area is very time consuming and even impossible in hazardous environment. One of the solutions to this problem is by using mobile robots with concern on exploration algorithm for mobile robot. In this thesis an autonomous deployment method for wireless sensor nodes is proposed via multi-robot system which robots are considered as nodes carrier. Developing an exploration algorithm based on spanning tree is the main contribution. The exploration algorithm should perform fast localization of sensor nodes in energy efficient manner. Employing a multi-robot system and path planning with spanning tree algorithm is a strategy for speeding up sensor node deployment. An improvement of this technique in deployment of nodes is the use of an obstacle avoidance mechanism without concern on shape and size of obstacle. The deployment task in this thesis is simulated on Player/Stage environment and the results were compared with other algorithms like obstacle-free and power-efficient (OFPE) which is modified to multi-robot (MR-OFPE) for deploying nodes. Using the proposed method, the results demonstrated an improvement in energy efficiency up to 40%, while deploying time is reduced about 28% compared to MR-OFPE. By deploying these nodes, the sensing coverage is enhanced about 8% compared to MR-OFPE. This research shows that a multi-robot system can optimize time and energy in robots while improving the application of a wireless sensor network.